Going Concern Audit Opinion on Manufacturing Companies in Indonesia - Meilda Wiguna; Hardi; Eka Hariyani (Jurnal Akuntansi Keuangan dan Bisnis, 2021)
Going concern is important issue to be addressed since it determine how the business will survive. This study is entitled "Going Concern Audit Opinion on Manufacturing Companies in Indonesia. Secondary data in this study are audited financial reports and annual financial reports of manufacturing companies listed on the IDX for the 2013-2017 period. The statistical method used in this study is logistic regression analysis, because in this study the independent variable is a mixture of continuous or metric variables. The results showed that audit tenure had no effect on going concern audit opinion. And the auditor's reputation does not have an influence on the company's decision makers in conducting going concern audit opinion. The debt default also affects going concern audit opinion. Keywords: Going Concern Audit Opinion, Audit Tenure, Auditor Reputation, Debt Default.